THE IMPLEMENTATION OF THE SPECIAL AUTONOMY OF PAPUA PROVINCE FROM THE ASPECT OF IMPROVING PUBLIC SERVICES - Purwoko Aji Prabowo; Bambang Supriyono; M.R. Khairul Muluk; Irwan Noor (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
This research is motivated by the implementation of special autonomy in Papua Province to overcome the unequal welfare problems compared to other provinces in Indonesia. The welfare issues raised in this study cover the fields of education, health, finance, and infrastructure. This research views the special autonomy policy of Papua Province as the formation of institutions, the transfer of authority, and financial management to improve the welfare of the community. Therefore, this study aims to explain the facts related to institutions, authority, and financial management in Special Autonomy in Papua Province to improve the welfare of the community. This research was conducted an assessment program activities approach and data collection through in-depth interviews and documents. Institutions and powers to make welfare include institutions and authorities in terms of education, health, finance, and infrastructure, each of which is carried out by the education office, health office, special autonomy bureau of the regional secretariat and regional financial and asset management agencies, and public works services. Meanwhile, financial arrangements in terms of education are carried out with formal and non-formal PAUD financial allocations (5%), 6-year compulsory basic education in elementary school (35%), 3 years of junior high school (25%), high school (10%), Vocational High Schools (5%), Non-formal and Informal Education (10%), other relevant Higher Education and Education (10%), health is carried out with a 15% fund allocation, the finance is carried out with a 25% fund allocation, and infrastructure is allocated funds of 20%.